Measurements and Theoretical Predictions of Charge Exchange Cross Sections and Emission Spectra for O6+ with H2O, CO, CO2, CH4, N2, NO, N2O and Ar. (July 2015) - Machacek, J R; Mahapatra, D P; Schultz, D R; Ralchenko, Yu; Moradmand, A; El Ghazaly, M O A; Chutjian, A
Synopsis: Relevant to modeling and understanding X-ray emission from cometary and planetary atmospheres, total charge-exchange cross sections for 1.17 and 2.33 keV/u O 6+ ions colliding with H2 O, CO, CO2, CH4, N2, NO, N2 O, and Ar have been measured and calculated for the processes of single, double, and triple exchanges. Synthetic emission spectra spanning the X-ray, UV, and visible ranges have also been calculated, based on theoretical treatment of the transfer of between one and six electrons from the target neutral to the projectile ion, followed by radiative and nonradiative decay of the resulting highly-excited projectile states.